A Neurolinguistic View of the Visual Stimulus Selection System and the Auditory Processing of Children's Language - Ni Luh Sukanadi; I Ketut Wardana; Putu Sri Astuti (Universitas Pendidikan Ganesha, 2022)
The question of whether the absorption and response of visual stimulation are more effective than the auditory stimulation of English sounds by Indonesian-speaking students has just been answered. This study aims to describe the mental system of visual excitatory selection of words and to hear the sounds of English and Indonesian laterally from a neurolinguistic perspective. This study applies a phenomenology-based qualitative descriptive approach. The informants of this study were 22 elementary school children. The method used to collect data in this study is the method of observation and literature with recording and note-taking techniques. The techniques used to analyze the data are statistical and descriptive analysis. The results of this study indicate that the response to word sight stimulation is longer than the sound auditory stimulus trigger. From the point of view of the lateral mechanism, the responses of elementary school students to Indonesian word stimuli in English are, on average, more extended than the period for responses to English word stimuli in Indonesian. It is due to the limitations of the English lexicon, factors outside the language, psychological conditions, and combinations of motor movements that interrupt the focus of word calling. The lateral processing system model of words and sounds contributes to the teacher as a guide for implementing teaching strategies.